Blockchain: Transparency and Security Technology in Economy 5.0 - Judijanto, Loso; Ekasari, Silvia; Al-Amin (International Journal of Social Science, Education, Communication and Economics, 2025)
Blockchain technology has emerged as a key pillar in the development of Economy 5.0, offering innovative solutions to increase transparency and security in economic transactions. The technology enables the recording of transactions to be immutable and easily traceable by all parties involved in the network, reducing the possibility of fraud and errors. In addition, with its ability to secure data through complex cryptography, blockchain provides high protection against cyberattacks and data manipulation. In addition to providing security and transparency, blockchain utilization also enables the automation of business processes through the use of smart contracts, as well as strengthening integration between economic sectors. Overall, the adoption of blockchain in Economy 5.0 promises to improve operational efficiency, drive innovation, and support more sustainable and inclusive economic development.